Physicochemical Characteristics of Cream Cheese Based on Different Ratios of Bromelin Enzyme and Rennet Enzyme: Karakteristik Fisikokimia Keju Krim Berdasarkan Perbedaan Rasio Enzim Bromelin dan Enzim Rennet - Ningrum, Sugiyati; Prayitno, Sutrisno adi; Yahya, Achmad Tantowi (Universitas Muhammadiyah Sidoarjo, 2024)
Milk belongs to the food group that is readily ruined and provides complete nutrients; therefore, adequate processing is necessary to extend its shelf life. One of the most popular dairy products is cream cheese. This cream cheese has a soft texture, a white color, and a savoury flavour. It can be used as a topping or a complimentary element. This objective of this study was to determine the differences effect in the ratio of bromelain and rennet enzymes on the physicochemical characteristics of cream cheese. The experimental design used in this research was a Completely Randomized Design (CRD) with the following treatments: 8% bromelain enzyme (P1); 8% rennet enzyme (P2); bromelain enzyme 7% + rennet enzyme 1% (P3); bromelain enzyme 4% + rennet enzyme 4% (P4); 1% bromelain enzyme + 7% rennet enzyme (P5) where each treatment will be repeated 3 times. Some of the parameters tested were yield, pH, water content, protein content, color degree and spreadability. Based on the effectiveness test to determine the best treatment, the highest value was obtained for the P4 treatment with a yield of 11.14%, pH value of 5.83, water content of 55.50%, protein content of 5.62%, color degree of 78.21, and spreadability of 3.50 cm.